Syrian consumers: beliefs, attitudes, and behavioral responses to internet advertising - Mahmoud, Ali Bassam (Business: Theory and Practice, 2013)
The goal of this research is to determine the dimensions of beliefs about internet advertising affecting Syrian consumers’ attitudes and behaviors towards internet advertising. The results indicate that Attitudes are influenced positively by information, and entertainment; and negatively by irritation and values’ corruption. Irritation positively influences consumers’ behaviors of leaving websites showing the ads. Entertainment positively influences consumers’ behaviors of clicking on internet ads for further information concerning advertised products. Attitude is found to fully mediate the relationships between beliefs of information, irritation, and values’ corruption and the behaviors clicking on internet ads, and partially mediate the relationship between entertainment and the behaviors of clicking on internet ads. Attitudes fully mediate the relationships between beliefs of information, entertainment, and values’ corruption and the behaviors of leaving websites showing the ads, and partially mediate the relationship between irritation and the behaviors of leaving websites showing the ads. This research comes to be one of the first studies to investigate Syrian consumers’ beliefs about, attitudes, and behavioral responses towards internet advertising. As well as, this study provides evidence of the direct relationship between some of the beliefs about internet advertising (i.e. entertainment and irritation) and the behavioral responses towards it.